Navigating Islamophobia: the tale of two Polands - Górak-Sosnowska, Katarzyna (Przegląd Krytyczny, 2022)
The paper analyses the Islamophobic and anti-refugee narratives in Poland through the lens of two different modes of patriotism. These two types of patriotism reflect a great division within Polish society – i.e. between openness and aspiration towards EU and closeness and pride from Polish history. Islamophobic and anti-refugee discourse are powerful tools used in contemporary political discourse by the ruling party, yet they exemplify only one of many layers of the division. The paper starts with setting the framework for Islamophobic discourse in Poland, namely lacking post-colonial reflection and cultural homogeneity. It uses the concept of social imaginary to analyse conflicting discourses on Muslims and refugees on three different examples: use of Polish history for as a source of integration vs. defence against allegations; welcoming refugees as European obligation vs. obligation of EU towards Poland, and endorsing multiculturalism vs. Poland as antemurale christianitatis.